Electrical conductance and structure of copper atomic junctions in the presence of water molecules. Issue 48 (20th November 2015) - Li, Yu; Demir, Firuz; Kaneko, Satoshi; Fujii, Shintaro; Nishino, Tomoaki; Saffarzadeh, Alireza; Kirczenow, George; Kiguchi, Manabu
Abstract : We have investigated Cu atomic contacts in the presence of H2 O both experimentally and theoretically. Abstract : We have investigated Cu atomic contacts in the presence of H2 O both experimentally and theoretically. The conductance measurements showed the formation of H2 O/Cu junctions with a fixed conductance value of around 0.1 G 0 ( G 0 = 2 e 2 / h ). These structures were found to be stable and could be stretched over 0.5 nm, indicating the formation of an atomic or molecular chain. In agreement with the experimental findings, theoretical calculations revealed that the conductance of H2 O/Cu junctions decreases in stages as the junction is stretched, with the formation of a H2 O/Cu atomic chain with a conductance of ca. 0.1 G 0 prior to junction rupture. Conversely, in the absence of H2 O, the conductance of the Cu junction remains close to 1 G 0 prior to the junction rupture and abrupt conductance drop.